Development of Wholesale and Retail Trade, Repair of Motor Vehicles and Motorcycles Business in Rangpur Division - Faruque, Omar; Rahman, Md. Motiur (ABC Journal of Advanced Research, 2021)
Bangladesh has already become a middle-income country. Yet its large number of working people is still jobless. The importance of Wholesale, Retail, Motor-vehicle workshop, and Motorcycle businesses (WRMB) for solving employment problems in a short time is immense. WRMB can pave the way for the employment of these people. There are eighteen types of manufacturing and service activity in the small-scale industry (SSI) sector. Out of this WRMB activity sector holds the height contribution in number. This paper attempts to discover the present situation of the Growth and Development of the Wholesale, Retail, Motor-vehicle workshops, and Motorcycle businesses in the Rangpur Division of Bangladesh during 2013-14 to 2017-18. The study is empirical. Both the primary and secondary data have been used in this study. Primary data is collected from 200 wholesale and retail trade, repair of motor vehicles, and motorcycles activity. The study found a simple correlation between financial conditions of the WRMB with the three dependent variables `net sales 2013-14’, `net sales 2017-18’, and `average net sales’.